Synthesis, antimicrobial, anticancer, antiviral evaluation and QSAR studies of 4-(1-aryl-2-oxo-1,2-dihydro-indol-3-ylideneamino)-N-substituted benzene sulfonamides - Mahesh Kumar; Kalavathy Ramasamy; Vasudevan Mani; Rakesh Kumar Mishra; Abu Bakar Abdul Majeed; Erik De Clercq; Balasubramanian Narasimhan (Arabian Journal of Chemistry, 2014)
A series of 4-(1-aryl-2-oxo-1,2-dihydro-indol-3-ylideneamino)-N-substituted benzenesulfonamide derivatives (1–32) was synthesized and evaluated for its in vitro antimicrobial, antiviral and cytotoxic activities. Antimicrobial results indicated that compounds (11) and (18) were found to be the most effective ones. In general, the synthesized compounds were bacteriostatic and fungistatic in their action. The cytotoxic screening results indicated that the compounds were less active than the standard drug 5-fluorouracil (5-FU). None of the compounds inhibited viral replication at subtoxic concentrations. In general, the presence of a pyrimidine ring with electron releasing groups and an ortho- and para-substituted benzoyl moiety favored antimicrobial activities. The results of QSAR studies demonstrated the importance of topological parameters, valence zero order molecular connectivity index (0χv) and valence first order molecular connectivity index (1χv) in describing the antimicrobial activity of synthesized compounds.